1998
DOI: 10.1152/ajpregu.1998.275.6.r2056
|View full text |Cite
|
Sign up to set email alerts
|

Renal effects of leptin in normotensive, hypertensive, and obese rats

Abstract: The hemodynamic, hormonal, and renal excretory effects of intravenous bolus administration of synthetic murine leptin were examined in groups of anesthetized normotensive (Sprague-Dawley), hypertensive (spontaneously hypertensive), and both lean and obese Zucker rats. In the normotensive animals ( n = 8) an intravenous bolus of 400 μg/kg of leptin produced a significant six- to sevenfold elevation in sodium excretion compared with controls ( n = 8). The onset of natriuresis was delayed for ∼30–45 min. Mean art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 24 publications
3
66
1
1
Order By: Relevance
“…Fasting did significantly increase PRA and aldosterone, however, but r-metHuLeptin did not alter these fasting-induced changes in the mineralocorticoid axis. These findings are in contrast to the effect of leptin administration on increase natriuresis (49,50) and sympathetic activity (51) in normal, nonobese leptin-resistant Zucker rats (51). Our findings are in agreement with a previous study in nonobese men on an isocaloric diet in whom leptin administration (0.3 mg/kg per day) for 6 days had no effect on autonomic activity or urinary catecholamines (52).…”
supporting
confidence: 90%
“…Fasting did significantly increase PRA and aldosterone, however, but r-metHuLeptin did not alter these fasting-induced changes in the mineralocorticoid axis. These findings are in contrast to the effect of leptin administration on increase natriuresis (49,50) and sympathetic activity (51) in normal, nonobese leptin-resistant Zucker rats (51). Our findings are in agreement with a previous study in nonobese men on an isocaloric diet in whom leptin administration (0.3 mg/kg per day) for 6 days had no effect on autonomic activity or urinary catecholamines (52).…”
supporting
confidence: 90%
“…In light of previous studies, 22,[32][33][34][35][36][37] there appears to be an intimate relationship through increased proximal tubular sodium reabsorption among high serum urate, resistance to the facilitatory effects of leptin on insulin sensitivity and renal sodium excretion, sympathetic hyperactivity, and hyperinsulinemia. In conclusion, our study is the first comprehensive and the largest study of the relationship between serum leptin and uric acid concentrations to date and suggests that leptin could be the missing link between obesity and hyperuricemia.…”
Section: Discussionmentioning
confidence: 87%
“…Reports of a positive correlation between leptin and PRA in obesity and essential hypertension in humans suggest a potential role for leptin in renin release (5,836,894), but up to now, no direct effect of leptin on the release of renin from the kidney has been reported. In contrast, the carotid artery or intravenous infusion of leptin did not alter PRA in rats (793,914). However, leptin may indirectly induce renin release via a central activation of the renal sympathetic nervous system (120, 323,561,711,712,910).…”
Section: Adipokines: Leptin and Adiponectinmentioning
confidence: 97%
“…Later on, it was observed that leptin also influences the cardiovascular and renal functions and that the increased levels of leptin in obesity may contribute to obesity-induced hypertension. It has been found, for example, that the infusion of leptin activates sympathetic nerve activity and increases the mean arterial blood pressure, heart rate, urine volume, and sodium excretion in rats (323,389,793,914). Reports of a positive correlation between leptin and PRA in obesity and essential hypertension in humans suggest a potential role for leptin in renin release (5,836,894), but up to now, no direct effect of leptin on the release of renin from the kidney has been reported.…”
Section: Adipokines: Leptin and Adiponectinmentioning
confidence: 99%